Analisis Komparasi Pendapatan Usahatani Sayuran Organik dan Sayuran Anorganik - La Iwe; Supiani Supiani; Sudarnice Sudarnice; Karlin Karlin (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the comparison of organic vegetable farming income with inorganic vegetables in Wawesa Village, Batalaiworu District, Muna Regency. The total population of this study were all organic vegetable farmers and inorganic vegetables in Wawesa Village, Batalaiworu District, Muna Regency, namely as many as 20 vegetable farmers. Of these, 10 organic vegetable farmers and 10 organic vegetable farmers were selected purposively. The data obtained were analyzed using quantitative analysis using t-test through Smart SPSS software. The results showed that there were differences in the income of organic vegetable farming and inorganic vegetables, where the income of inorganic vegetable farming was greater than the income of organic vegetable farming. This can be proven by the value of t-count < t-table (-10.398 < -2.262).